QUALITY OF SERVICE ACTIVITIES FUNCTIONAL FACILITIES IN FISHINGPORT HEADMAN PURNAMA,SUB-DISTRICT WEST DUMAI, DUMAI CITY RIAU PROVINCE - Fivi Fransisca Simamora; Jonny Zain; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe Dumai Fish Landing Base is the only active fishing port used in Dumai City so it should be able to accommodate all the activities carried out by fishermen in Dumai City in order to be able to increase fisheries production. Therefore, to see the quality of service activities for its functional facilities, it is necessary to know whether in its service, managers and fishermen make Standard Operating Procedures as the standard rules and with the application of existing Standard Operating Procedures, whether fishermen are satisfied. The purpose of this study is to determine the quality of service activities for functional facilities. The study was conducted at the Dumai Fish Landing Base on March 25 - April 6, 2019. The method used in this study was a survey method, which was conducted by collecting facility data, organizational structure, Standard Operating Procedures and Implementing Standard Operating Procedures. Data collection is carried out at the Fish Auction, Ice Factory and SPDN facilities. After analyzing the data with the Guttman scale and the Likert scale, the results show that the implementation of Standard Operating Procedures in the three functional facilities is applied 100%. While the quality of service at the Fish Auction Place facilities is 68.98% (good), the Ice Factory facility is 43.86% (not good) and the SPDN facility is 99.52% (very good). Key word: Fishing Port, Dumai Fishing Port, Standard Operating Procedure, Service Quality